GAMBARAN PENGETAHUAN, SIKAP DAN PRAKTIK PENCEGAHANKEKERASAN SEKSUALTERHADAP ANAK PADA KETERPAPARAN PROGRAM YAYASAN SETARA DENGAN MEDIA VIDEO (Studi Kasus di 2 SD di Kota Semarang) - Theresia Evelyn; Atik Mawarni; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2016)
Center for intergrated service of treating women and child abuse gender based (PPT Seruni) Semarang handled 93 cases of child abuse (2015) consisted of 48 cases of children sexual abuse. This data was increasing compared to 75 complaints of child abuse in 2014 which consisted of 52% children sexual abuse cases. Yayasan Setara Semarang is one of foundations that concerns to children’s rights. In doing so, Yayasan Setara Semarang provides a program for the children by playing some preventing children sexual abuse sosialization videos made by UNICEF in collaboration with Ministry of Health RI.  The video told about what a child must do and must not do things as a respond to an older’s action toward the children. The prupose of this research is to describe knowledge, attitude and practice of preventing children sexual abuse based on Yayasan Setara Semarang’s Program exposure by using video. The type of this research is descriptive study. The population of this research is student who had been exposed in SDN 03 and 04 Jomblang. The data was analyzed by descriptive analysis. The analysis showed that respondents’ knowledge was lacking because of the video has not contained potentially children sexual abuse perpetrators in the video, respondents’ atittude can be increased by adding other’s children sexual abuse potentially actions they should avoid in the video and respondents’ practice can be increased by adding they must not do things toward other older in the video. The result of this research suggests Department of Education to insert preventing children sexual abuse matters into school’s curriculum and Yayasan Setara to develop the program into demonstration and brainstorming form.